2023
DOI: 10.1089/cap.2022.0076
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Serdexmethylphenidate/Dexmethylphenidate Capsules in Children with Attention-Deficit/Hyperactivity Disorder: A 12-Month, Open-Label Safety Study

Abstract: Objective: Serdexmethylphenidate/dexmethylphenidate (SDX/d-MPH) is approved for the treatment of patients aged ≥6 years with attention-deficit/hyperactivity disorder (ADHD). A pivotal double-blind (DB) study of children aged 6–12 years with ADHD demonstrated efficacy for ADHD with good tolerability. In this study, we assessed the safety and tolerability of daily oral SDX/d-MPH for up to 1 year in children with ADHD. Methods: This was a dose-optimized, open-label safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Some recent publications confirm the safety of stimulants regarding this matter of discussion. A recent analysis of Growth Velocity in ADHD Children medicated with Serdexmethylphenidate/Dexmethylphenidate for 12 months confirm that the effects of medication on height were minimal and not clinically significant (Childress et al, 2023) while our previously reported findings from the full ADDUCE prospective study found no evidence of an MPH effect on height in the medicated population compared to the No-MPH group in the long-term (24 months); only for weight velocity there was an initial slowing at 6 months in the MPH group with no group differences for BMI at any time point (Man et al, 2023).…”
Section: Discussionmentioning
confidence: 97%
“…Some recent publications confirm the safety of stimulants regarding this matter of discussion. A recent analysis of Growth Velocity in ADHD Children medicated with Serdexmethylphenidate/Dexmethylphenidate for 12 months confirm that the effects of medication on height were minimal and not clinically significant (Childress et al, 2023) while our previously reported findings from the full ADDUCE prospective study found no evidence of an MPH effect on height in the medicated population compared to the No-MPH group in the long-term (24 months); only for weight velocity there was an initial slowing at 6 months in the MPH group with no group differences for BMI at any time point (Man et al, 2023).…”
Section: Discussionmentioning
confidence: 97%
“…13 Though stimulant, it has lower abuse potential and less severe adverse effect profile. 14,15,16 Viloxazine:Previously used as antidepressant, it is a non-stimulant drug, approved by FDA in April, 2021 for use in ADHD. 17 It acts via selectively inhibiting norepinephrine reuptake and has low abuse potential with adverse effects similar to non-stimulants.…”
Section: Pharmacotherapy a Fda Approved In Last 3 Yearsmentioning
confidence: 99%
“…Some studies have shown beneficial effects of MPH on sleep in patients with ADHD with pre-existing sleep disturbances (6,7). Others have reported a more complicated relationship between MPH treatments and sleep in the ADHD patient population because the formulation and dose of MPH, length of treatment, measures of sleep (e.g., objective vs. subjective measures), and the patient population (e.g., inclusion of patients with sleep problems prior to treatment or those without any pre-existing sleep problems) can vary from study-tostudy (6,8) A subsequent 1-year, open-label, dose-optimized safety study of SDX/d-MPH showed that SDX/d-MPH was well tolerated with no new or unexpected safety findings and had sustained effectiveness in reducing ADHD symptoms during the 1-year treatment period in children age 6 to 12 years with ADHD (10). Of 238 participants assessed during the 12-month treatment phase of the study, the most common treatment-related AEs were decreased appetite (18.5%), upper respiratory tract infection (9.7%), nasopharyngitis (8.0%), decreased weight (7.6%), and irritability (6.7%).…”
Section: Introductionmentioning
confidence: 99%